PENGARUH WARNA TERHADAP KAMAR TIDUR ANAK - Setyohadi KP, RM. Bambang (Semarang State University, 2010)
Stock colors are very influential to the psychology of room occupants, because the bedroom is a very personal space. Each resident room has character, lifestyle, and needs vary. Color also depends on the age of room occupants. Color also has character and personality that makes it different from each other. Color can create a certain impression can even affect human feelings. Childhood is very long in the span of his life, because at that time someone has to know the objects and colors that have never known. During this period a person will also learn about life. Color is one of the media to develop the imagination, especially the children who are still in the development. The ideal child's bedroom is a room safe, healthy, and can stimulate creativity and develop a child's imagination. How to choose furniture and interior knacks appropriate, arrange furniture, and make use of lighting in accordance with the age of the child so the child comfortable in his room so as to create a child's room a charming, comfortable and able to meet some aspects such as function rooms, health, safety, psychological, and other aspects. For the bedroom children aged 6-12 years tend to use natural color and color of